Kerjasama Indonesia dan Denmark dalam Membangun Energi Terbarukan di Sulawesi Selatan (Pembangkit Listrik Tenaga Bayu PLTB di Jeneponto) - Muksin, Nur Izza Zakiatul; Rahmi, Rahmi; Amsir, Ahmad abdi (Universitas Muhammadiyah Sorong, 2024)
This research aims to understand in depth the mechanisms and results of cooperation between Indonesia and Denmark in the construction of a Wind Power Plant (PLTB) in Jeneponto, South Sulawesi. The type of research used in this research is field research, using qualitative research methods carried out through interviews with resource persons. This research also uses several data sources obtained through library research such as books, journals, mass media, official websites of government institutions related to this research. This research uses the concept of international cooperation and green politics theory which are used as references in explaining the research results in this study. The results of this research explain the impact of cooperation between Indonesia and Denmark on the construction of the Wind Power Plant (PLTB) in Jeneponto. The results of this research are that the collaboration between Indonesia and Denmark in the construction of the Wind Power Plant (PLTB) in Jeneponto has had a positive impact and sustainable. These results show that international collaboration based on commitment and shared goals can have a major contribution in advancing the renewable energy sector in Indonesia.